2022
DOI: 10.1007/s10637-022-01283-x
|View full text |Cite
|
Sign up to set email alerts
|

Real-world data on efficacy and safety of azacitidine therapy in chronic myelomonocytic leukemia in China: results from a multicenter, retrospective study

Abstract: SummaryChronic myelomonocytic leukemia (CMML) is a rare and aggressive myeloid malignancy with overlapped features of myelodysplastic syndromes/myeloproliferative neoplasms. Azacitidine (AZA), a hypomethylating agent, has been approved for the treatment of CMML in China, but real-world data are limited. Medical records of CMML patients who had received subcutaneously injected AZA were reviewed from January 2018 at five participating sites in China. Response was assessed according to the modified International … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…According to CMML epidemiological statistics, almost 90% of cases occur in patients older than 60 years 4,35,50 . We reviewed the literatures on the age of CMML patients in Western (Germany, 29,30,51 France, 13,19,52 America, 8,11,12,15,17,20,25,26,28,40,53,54 Italy, 39,55 Greece, 14 and Denmark, 24 ) and Eastern countries (Japan 16,22,27 and China, 6,43,49,56–63 ), and the results showed that the median age of CMML patients in Eastern countries was younger (38–70 years vs. 44–73 years), and the median age of CMML patients undergoing allo‐HSCT was similar in Eastern and Western countries (38–63 years vs. 44–64 years). However, the age of CMML patients undergoing allo‐HSCT was lower in both Eastern and Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…According to CMML epidemiological statistics, almost 90% of cases occur in patients older than 60 years 4,35,50 . We reviewed the literatures on the age of CMML patients in Western (Germany, 29,30,51 France, 13,19,52 America, 8,11,12,15,17,20,25,26,28,40,53,54 Italy, 39,55 Greece, 14 and Denmark, 24 ) and Eastern countries (Japan 16,22,27 and China, 6,43,49,56–63 ), and the results showed that the median age of CMML patients in Eastern countries was younger (38–70 years vs. 44–73 years), and the median age of CMML patients undergoing allo‐HSCT was similar in Eastern and Western countries (38–63 years vs. 44–64 years). However, the age of CMML patients undergoing allo‐HSCT was lower in both Eastern and Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…The two FDA-approved de-methylating compounds for CMML, azacitidine (AZA) and decitabine (DEC) were initially designed to restore the disordered epigenetics in malignant HSPCs, which were thought to be disease-promoting consequences of genetic lesions involving epigenetics (2). However, demonstrated by the limited inhibitory effect on malignant clones in patients, HMAs may not produce e cacies prominently through the direct anti-tumor effect (7)(8)(9)(10). Those post-HMA therapeutic responses (e.g., hematological improvement) (11) are more likely attributed to the selective promotion of residual healthy hematopoiesis in the bone marrow.…”
Section: Introductionmentioning
confidence: 99%